Energy Harvesting in Nanosystems: Powering the Next Generation of the Internet of Things - Phillips, Jamie D. (Frontiers in Nanotechnology, 2021)
Untethered, wirelessly interconnected devices are becoming pervasive in today's society forming the Internet of Things. These autonomous devices and systems continue to scale to reduced dimensions at the millimeter scale and below, presenting major challenges to how we provide power to these devices. This article surveys existing approaches to harvest energy from the ambient or externally supplied sources including radio-frequency, optical, mechanical, thermal, nuclear, chemical, and biological modalities to provide electrical power for micro- and nano-systems. The outlook for scaling these energy conversion approaches to small dimensions is discussed in the context of both existing technologies and possible future nanoscience developments.